Damped oscillating traveling waves of a diffusive SIR epidemic model. (August 2015) - Li, Yan; Li, Wan-Tong; Lin, Guo
Abstract: This paper is concerned with the damped oscillating traveling waves of a diffusive SIR model with vital dynamics. Our result implies that the vital dynamics can induce damped spatio-temporal oscillations. Biologically, this shows that the vital dynamics can cause multiple outbreaks of infection with decreasing maximum outbreak sizes.